Segmental and descending control of primary afferent input to the spinal lamina X - Krotov, Volodymyr; Agashkov, Kirill; Krasniakova, Marharyta; Safronov, Boris V.; Belan, Pavel; Voitenko, Nana (Pain (Amsterdam), 2022)
Despite being involved in a number of functions, such as nociception and locomotion, spinal lamina X remains one of the least studied central nervous system regions. Here, we show that Aδ- and C-afferent inputs to lamina X neurons are presynaptically inhibited by homo- and heterosegmental afferents as well as by descending fibers from the corticospinal tract, dorsolateral funiculus, and anterior funiculus. Activation of descending tracts suppresses primary afferent-evoked action potentials and also elicits excitatory (mono- and polysynaptic) and inhibitory postsynaptic responses in lamina X neurons. Thus, primary afferent input to lamina X is subject to both spinal and supraspinal control being regulated by at least 5 distinct pathways.